SEXUAL DISTURBANCES IN WOMEN DURING THE PERIMENOPAUSAL PERIOD - Kayumova, D.T.; Urolova, U.S. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Purpose of the study is to identify the primary causes of sexual disturbances in women during the perimenopausal period, specifically hormonal changes, psychological factors, physical symptoms, and relationship changes, as well as to explore effective approaches to managing these issues (hormone therapy, psychological support, lifestyle changes). Material and methods. This study was conducted to explore the causes of sexual disturbances in women during perimenopause, their impact, and methods for managing them. A combination of quantitative and qualitative methods was used, providing a comprehensive analysis of the issue. The study focused on identifying the factors affecting sexual health in women during perimenopause and examining effective management strategies for these disturbances. Conclusion. Sexual disturbances are common among women during perimenopause. Hormonal changes, such as a decrease in estrogen levels, lead to vaginal dryness and reduced sexual desire. Psychological factors, such as mood swings and lowered self-esteem, can negatively affect sexual health. Physical symptoms, such as hot flashes and insomnia, also reduce sexual interest. Sexual disturbances impact relationships as well, requiring open communication and professional assistance. Treatment methods, including hormone therapy, vaginal moisturizers, and pelvic floor exercises, help alleviate discomfort during intercourse. Regular physical activity, stress management, and proper nutrition also play a crucial role in improving sexual health. With the right support, women can successfully navigate this period.